The Visualization Simulation Platform Development for OFDM-Based Visible Light Communication in Indoor Application - Chuang, KwangSeng; Talib, Rahmat (Evolution in Electrical and Electronic Engineering, 2021)
In the VLC system study, simulation and prototype development are the important processes to build up an OFDM-based visible light communication system for indoor application. However, prototype development is time-consuming and costly. This paper proposed a MATLAB graphical user interface (GUI) for orthogonal frequency division multiplexing (OFDM) based visible light communication in a room dimension of 6m*6m*3.5m. For the proposed GUI, visible light modelling was employed to obtained received power from line-of sight and first reflection from wall by considered average power transmitted per LED was 115mW. Then total received power is used to investigate the signal-to-noise ratio (SNR) and calculated the bit error rate (BER) based on the 4-QAM modulation technique. In addition, the delay spread profile is examined. The simulation results showed that transmitters’ position along the x-axis given the lowest delay spread profile compared to axis-excited topology and corner-excited topology. In the future, the application of indoor positioning could be added to increase the functionalities of GUI.  Further performance analysis possible to be included are the SNR, BER and indoor positioning accuracy.